Asymmetric cross-coupling of alkyl, alkenyl and (hetero)aryl nucleophiles with racemic allyl halides. Issue 93 (3rd November 2017) - Schäfer, Philipp; Sidera, Mireia; Palacin, Thomas; Fletcher, Stephen P.
Abstract : Highly enantioselective transition metal catalyzed asymmetric cross-coupling reactions of cyclic allyl halides non-stabilized nucleophiles. Abstract : Single enantiomer molecules are important for the pharmaceutical and agrochemical industries and increasingly so in materials science. Most strategies to obtain enantiomerically enriched molecules rely on either generating new stereogenic centres from prochiral substrates or resolving racemic mixtures of enantiomers. Dynamic asymmetric processes are powerful methods that use racemic mixtures of chiral substrates as starting material. This Feature Article focuses on asymmetric additions to racemic substrates using non-stabilized sp 2 - and sp 3 -hybridized nucleophiles. These reactions bear considerable resemblance to traditional sp 2 –sp 2 cross-coupling reactions in terms of the starting materials used and the products obtained, but the reaction mechanisms are necessarily different.